Investment Decisions in Global Financial Markets: the Experience of Lithuania - Aleksandras Vytautas Rutkauskas; Alina Kvietkauskienė (Entrepreneurial Business and Economics Review)
The objective of this article is to identify the content of globalization processes in financial markets. The universal method of investment is offered in order to save the interests of investors – to expand the geography of investment, not leaving without attention innovative activities. This method has become global in financial market segment and thus strengthening the financial system's ability to contribute significantly to the globalization, sustainability and cost-effectiveness of education. Findings present sustainable return on investment possibilities. The analysed indicator is expected investment value, measured with a certain size of return and composition of reliability maximization.